2015
DOI: 10.1016/j.scitotenv.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the contribution of photochemical particle formation to ultrafine particle number averages in an urban atmosphere

Abstract: Ultrafine particles (UFPs, diameter<100 nm) have gained major attention in the environmental health discussion due to a number of suspected health effects. Observations of UFPs in urban air reveal the presence of several, time-dependent particle sources. In order to attribute measured UFP number concentrations to different source type contributions, we analyzed observations collected at a triplet of observation sites (roadside, urban background, rural) in the city of Leipzig, Germany. Photochemical new particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 48 publications
6
47
0
1
Order By: Relevance
“…Power station plumes contain primary UFPs and excess secondary particle precursor substances H 2 SO 4 and ammonia. They are also consistent with the regional variability and temporal evolution of boundary layer UFP number concentrations and size distributions in urban and rural environments in Germany (Birmili et al, 2013;Ma and Birmili, 2015). A dominating role of three-dimensional transport processes on the distribution of aerosols a regional scale on has been observed also elsewhere in larger aerosol network studies (Demerjian and Mohnen, 2008).…”
Section: Summary and Discussionsupporting
confidence: 83%
“…Power station plumes contain primary UFPs and excess secondary particle precursor substances H 2 SO 4 and ammonia. They are also consistent with the regional variability and temporal evolution of boundary layer UFP number concentrations and size distributions in urban and rural environments in Germany (Birmili et al, 2013;Ma and Birmili, 2015). A dominating role of three-dimensional transport processes on the distribution of aerosols a regional scale on has been observed also elsewhere in larger aerosol network studies (Demerjian and Mohnen, 2008).…”
Section: Summary and Discussionsupporting
confidence: 83%
“…It is recognised that it may be limited in terms of giving exhaustive consideration and quantification of each individual driver on pollutant concentration, particularly the complex influence of local street topography. The absence of summer measurements could mean that the influence of photochemical particle formation may be underestimated (Ma and Birmili, 2015). Overall, however, this study has demonstrated that careful experimental design and data interpretation of short-term mobile measurements can identify the important drivers governing different metrics of PM concentration, and which also support findings in literature that use more sophisticated long term measurements.…”
Section: Study Limitationssupporting
confidence: 79%
“…Furthermore, Brines et al (2015) calculated that 22 % of the annual average UFP number concentration recorded at an urban background site of Barcelona originated from NPF. Ma and Birmili (2015) reported that the annual contribution of traffic on UFP number concentration was 7, 14 and 30 % at roadside, urban background and rural sites respectively, in and around Leipzig, Germany. On the other hand, traffic emissions 10 contributed 44-69 % to UFP concentrations in Barcelona (Pey et al, 2009;Dall'Osto et al, 2012, 65 % in London (Harrison et al, 2011;Beddows et al, 2015) and 69 % in Helsinki (Wegner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tröstl et al (2016) reported experimental results on nucleation driven by oxidation of Volatile organic compounds (VOCs), and Kirkby et al (2016) reported pure biogenic nucleation. Globally, and 15 especially in urban areas, traffic emissions are a major source of UFP Ma and Birmili, 2015;Pey et al, 2008;Pey et al, 2009;Dall'Osto et al, 2012;Salma et al, 2014;Paasonen et al, 2016) and these arise from primary UFP exhaust emissions (Shi and Harrison, 1999;Shi et al, 2000;Charron and Harrison, 2003; Uhrner et al, 2012), condensation of semi-volatile phases vapor species that creates new UFP during dilution and cooling of engine exhaust emissions near the source (Charron and Harrison, 2003;Kittelson et al, 2006;Robinson et al, 2007). Since these are formed very close to the 20 source, most studies consider them as primary (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation